Genetic variation in sex-steroid receptors and synthesizing enzymes and colorectal cancer risk in women - Lin, Jennifer; Zee, Robert Y. L; Liu, Kuang-Yu; Zhang, Shumin M; Lee, I-Min; Manson, JoAnn E; Giovannucci, Edward; Buring, Julie E; Cook, Nancy R (Cancer causes & control, 2010)
Objectives Several lines of evidence have suggested that female hormones may lower the risk for developing colorectal cancer. However, the mechanisms by which sex hormones affect colorectal cancer development remain unknown. We sought to determine whether the association may be under genetic control by evaluating genetic variation in estrogen receptors (ESR1 and ESR2), progesterone receptor (PGR), aromatase cytochrome 450 enzyme (CYP19A1), and 17 beta-hydroxysteroid dehydrogenase type 2 gene (HSD17B2). Methods We included 158 incident cases of colorectal cancer and 563 randomly chosen control subjects from 28,345 women in the Women's Health Study aged 45 or older who provided blood samples and had no history of cancer or cardiovascular disease at baseline in 1993. All cases and controls were Caucasians of European descent. A total of 63 tagging and putative functional SNPs in the 5 genes were included for analysis. Unconditional logistic regression was used to estimate odds ratio (ORs) and 95% confidence intervals (CIs). Results There was no association between variation in ESR1, ESR2, PGR, CYP19A1 and HSD17B2 and colorectal cancer risk after correction for multiple comparisons (p values after correction ≥0.25). There was also no association with any of the haplotypes examined (p ≥ 0.15) and no evidence of joint effects of variants in the 5 genes (p ≥ 0.51). Conclusion Our data offer insufficient support for an association between variation in ESR1, ESR2, PGR, CYP19A1, and HSD17B2 and risk for developing colorectal cancer.